The evaluation of Virginiamycin in feed as a treatment for swine dysentery in heavy (more than 120 lbs.) hogs - Schoneweis, D.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Virginiamycin at 100 grams per ton of feed was effective as a treatment against swine dysentery. The only pig receiving Virginiamycin that died during treatment had concurrent gangrenous pneumonia --probably the major cause of death. The pigs receiving the feed with Virginiamycin were more alert and ate more than the controls--which resulted in more weight gain and improved feed conversion. The Virginiarnycin did not clear up all signs of dysentery as several pigs continued to have diarrhea. Pigs that had been on Virginiamycin began to break with dysentery six days after the antibiotic was withdrawn and a pig weighing 234 pounds died of acute swine dysentery on the eleventh day of the observation period. This experiment using heavy finishing pigs indicated that Virginiamycin was effective as a treatment, but that it should be fed continually up to slaughter after a recent acute outbreak of swine dysentery.
Keywords: Swine; Virginiamycin; Dysentery